Policy Impact Divergence: Multiple Model Regression Analysis of Ghana’s ‘Free’ Maternal Health Care Policy - Azaare, John; Abdulai, Kasim; Bio, Robert Bagngmen (Disease and Health Research - New Insights Vol. 1, 2024)
Background: In July 2008, Ghana introduced a ‘free’ maternal health care policy (FMHCP) through the National Health Insurance Scheme (NHIS) to provide comprehensive antenatal, delivery and post-natal care services to mothers and their newborns. Although the ‘free’ policy was originally targeting equity in access to maternal health care, critics observed that the ‘free’ policy made no plan of responsiveness and quality of care for the unborn and the newborn. Methods: In a series of analyses, we evaluated the FMHCP impact on maternal healthcare utilization since the policy inception and then estimated the percentage point differences of stillbirth and early neonatal mortality among mothers who benefitted from the policy versus their counterparts who did not. The study used two rounds of historical data from the Ghana Demographic and Health Survey (GDHS, 2008–2014) and constructed the exposure variable of the FMHCP using mothers’ national health insurance status as a proxy variable and another group of mothers who did not subscribe to the ‘free’ policy. We then generated the propensity scores of the two groups, ex-post, and matched them to determine the impact of the ‘free’ policy as an intervention on antenatal care uptake and facility-level delivery utilization, using probit and logit models. Our analysis further constructed binary outcomes of stillbirth and perinatal mortality from the under-five mortality data of Ghana’s DHS data sets. We applied sample weighting across all analyses to account for clustering and stratification due to the complex design nature of DHS design. All regression analysis accounted for confounding variables using maternal individual characteristics deemed statistically significant, alpha value set at p < 0.005. Results: We found antenatal care uptake and facility level delivery increased markedly by 8 and 13 percentage points differences and these were statistically significant; observed coef., 0.08; CI: 95% [0.06–0.10]; p < 0.001 and 0.13; CI: 95% [0.11–0.15], p < 0.001, respectively. Pregnant women were 1.97 times more likely to make 4+ antenatal visits [WHO recommended minimum number of visits at the time] aOR = 1.97; CI: 95% [1.61–2.4]; p < 0.001 and 1.28 times more likely to make 8+ antenatal care visits (WHO current recommended minimum number of visits); aOR: 1.28; CI: 95% [1.10-1.49]; p < 0.001. The study also found that pregnant women were 1.87 times more likely to give birth in a healthcare facility of any level in Ghana between 2008 and 2014; aOR = 1.87; CI: 95% [1.57–2.23]; p < 0.001. Yet, stillbirth and early neonatal mortality were high showing 12 and 13 percentage points differences in the treatment group, compared to the no-treatment group and the differences were statistically significant; p = 0.005, respectively. Conclusions: In equity terms, the ‘free’ maternal health policy has made significant strides towards maternal healthcare utilization. However, this does not translate to the desired impact of the decrease in stillbirth and early neonatal mortality in its current form in Ghana.